Analysis of the Effect of Sharia Supervisory Board (SSB) Function on Earning Quality of Islamic Banks - Grandis Imama Hendra (Tazkia Islamic Finance and Business Review, 2016)
Analysis of the Effect of Sharia Supervisory Board (SSB) Function on Earning Quality of Islamic Banks Grandis Imama Hendra, MSACCLecturer of Islamic Accounting, STEI TazkiaABSTRACT Objective - This study aims to identify the effect of Sharia Supervisory Board (SSB) function on the level of earnings quality in Indonesian Islamic banks. SSB criteria used in this study are size, frequency of Meeting and educational background (Finance / Accounting). Method - Panel data regression is employed to analyze the effect of Sharia Supervisory Board characteristics on the earning quality of Islamic bank. The data were taken from 11 full-fledge Islamic banks in Indonesia with available financial statements from period 2010 to 2015.  Results - The size of Sharia Supervisory Board members has a positive effect on the improvement of earning quality in Islamic banking. Two other variables, namely the frequency of SSB meetings and educational background do not affect the improvement of earnings quality. Conclusion - Studies of the role of Sharia Supervisory Board to the quality of financial statements is still limited, especially in the quality of earning that became the basis in determining the distribution of Islamic banks profit sharing. The main contribution in this research is that the role of SSB should be improved in order to increase the quality of financial reporting. Keyword: Quality of profit, Sharia Supervisory Board (SSB), Sharia/Islamic Bank.